Carve-outs under airline antitrust immunity - Jan Keith Brueckner; Stef Proost (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper offers the first formal economic analysis of carve-outs under airline antitrust im- munity. Carve-outs are designed to limit the potential anticompetitive effects of cooperation by alliance partners in hub-to-hub markets, where they provide overlapping nonstop service. While the paper shows that carve-outs are beneficial when the alliance does not involve full integration of the partners' operations on the hub-to-hub route, its key point is that a carve-out may be harmful when imposed on a joint-venture alliance. A JV alliance involves full exploitation of economies of traffic density on the hub-to-hub route, and a carve-out prevents the realization of these benefits. While a carve-out may limit anticompetitive incentives on the hub-to-hub route, welfare may be reduced if the resulting gains are overshadowed by the efficiency loss generated by the carve-out.
Keywords: L40; 330; carve-out; alliance; antitrust immunity; airlines; Luftverkehrsgesellschaft; Strategische Allianz; Internationale Unternehmenskooperation; Konzentrationspolitik; Luftverkehr; Hub-and-Spoke System; Unternehmensentflechtung; Wohlfahrtseffekt; Theorie